Association between axial elongation and corneal topography in children undergoing orthokeratology with different back optic zone diameters - Qi Tan; Randy Kojima; Pauline Cho; Stephen J. Vincent (Eye and Vision)
Abstract Purpose To explore the associations between myopia defocus dosage (MDD), aberration coefficients (primary spherical aberration and coma), and axial elongation in children undergoing orthokeratology (ortho-k) with back optic zone diameters (BOZD) of 5 mm and 6 mm over 2 years. Methods Data from 80 participants from two ortho-k studies were analyzed: 22 and 58 children wore lenses with 5-mm and 6-mm BOZD, respectively. Four MDD metrics were calculated from corneal topography data over a 5-mm pupil for the 1-month and 24-month visits: the circumferential, flat, steep, and volumetric MDD. Corneal primary spherical aberration and comatic aberrations were also extracted from topography data over a 5-mm pupil. Linear mixed modelling was performed to explore the associations between the MDD, corneal aberrations, and axial elongation over 2 years, while controlling for confounding factors (e.g., baseline age and sex). Results Participants in the 5-mm BOZD group displayed less axial elongation than the 6-mm BOZD group over 2 years (0.15 ± 0.21 mm vs. 0.35 ± 0.21 mm, P < 0.001). A greater volumetric MDD was observed in the 5-mm BOZD group compared with the 6-mm BOZD group at the 1- and 24-month visits (both P < 0.001). No significant differences were observed between the two groups for the other MDD metrics or corneal aberration coefficients (all P > 0.05). Less axial elongation was associated with a greater volumetric MDD at the 1- and 24-month visits (both β = –0.01, P < 0.001 and P = 0.001), but not with any other MDD metrics or corneal aberrations (all P > 0.05). Conclusions The volumetric MDD over a 5-mm pupil after 1 month of ortho-k lens wear was associated with axial elongation after 24 months, and may be a useful predictor of future axial elongation in children undergoing ortho-k.